Restoring the Clinical Learning Environment at Teaching Hospitals in Post-Assad Syria: A PHEEM Analysis and Recommendations [version 2; peer review: 2 approved] - Amer Al Munajjed; Rama Kodmani; Ghaith Alfakhry; Rawan Khwanda; Munir Ghandour (MedEdPublish)
Introduction After 54 years of Assad’s family dictatorship, Syria was finally free but, nonetheless, was in ruins. The health profession education system is no exception, and there have been many indicators of this in the literature, but none of them have provided a systematic evaluation of the clinical learning environment (CLE) using validated approaches. Therefore, this study aimed to evaluate CLE at teaching hospitals in Damascus, Syria. Methods This cross-sectional study was conducted in Damascus, Syria, during mid-2023, before Assad’s regime collapsed. The study population included all residents working and training at any teaching hospital in Damascus. We used the recently validated 36-item Arabic-version of PHEEM inventory as a data collection tool and added 10 extra items related to Syria’s specific context. There was also one open-ended question. We recruited participants from 14 different teaching hospitals using nonprobability sampling techniques. Results A total of 1490 residents from 31 medical specialties participated in the study, which was approximately 37% of the total study population at that time. The female participants comprised 50.7% (n=754) of the total sample. Cronbach’s alpha was 0.925. The total PHEEM mean score was 72.4ŷ21.4 (Max. 144). All the PHEEM domains showed significant shortcomings, except for learner engagement and social participation. The worst-scoring domains were external regulation, work culture, and living conditions, with scores of 48.5%, 40.8%, and 31.2%, respectively. Responses showed that only 14% of respondents did not have plans to migrate. The written comments re-echo some of the PHEEM findings in more detail. Discussion This study draws a roadmap for clinical educators, lawmakers, and new leaders to make targeted reforms and investments to restore the clinical learning environment. There are major issues that not only render training residents suboptimal but also compromise residents' and patients’ safety.